How do brand evaluations affect online brand engagement? Mediation impact and evidence from Facebook - Alqahtani, Abdul; Sharma, Piyush; Davcik, Nebojsa; Kingshott, Russel (2024)
The research explores how electronic word-of-mouth (EWOM) messages on Facebook affect the brand evaluation and engagement of airline passengers. The Elaboration Likelihood Model (ELM) of persuasion theory is used to examine how message characteristics such as credibility and valence impact brand evaluation and engagement. An experiment was conducted with 480 airline travellers to test how different EWOM message formats (text, picture, audio-visual, audio) influence brand evaluation and engagement. The experiment comprised of 16 conditions. The key findings of the study are as follows: - Positive messages lead to better brand evaluation and, subsequently, increased engagement. - Credibility alone does not drive brand evaluation, and it does not mediate the relationship between message credibility and online brand engagement. - Textual EWOM format is the most effective format for positively influencing brand evaluation compared to other formats. The study is a significant contribution to the theory and practice of EWOM. It showcases the mediating role of brand evaluation and the importance of message valence and format. It also guides marketers on how to use EWOM effectively to improve online brand engagement. Keywords: brand evaluations, online brand engagement, Facebook, EWOM, travellers